Semantic based visualization - Larrea, Martín Leonardo (2006)
Visualization is the process of mapping data into visual dimensions to create a visual representation to amplify cognition. A successful visualization allows the user to gain insight into the data in other words to communicate different aspect of the data in an effective way. Even with today’s visualization systems that give the user a considerable control over the visualization process, it can be difficult to produce an effective visualization. A strategy to improve this situation is to guide the user in the selection of the parameters involved in the visualization. Our system goal of the research describe in this work is to develop a visualization that can be adapted to all data domains. By considering the semantic of the data together with the semantic of the stages through the visualization process it is intended to determinate all the characteristics of an effective visualization. This will guide the user through the stages of the visualization pipeline.